154k views
3 votes
7[x+3]+2[x+3] HELPPPPPPPP

User AVAVT
by
4.8k points

2 Answers

3 votes

Answer:

9x+27

Explanation:

7x+21+2x+6

9x+27

6 votes

Answer:


\sf9x + 27

Explanation:

Given expression,

→ 7(x + 3) + 2(x + 3)

Let's simplify the expression,

→ 7(x + 3) + 2(x + 3)

→ 7x + 21 + 2x + 6

→ (7x + 2x) + (21 + 6)

9x + 27

→ 9(x + 3)

Hence, answer is 9x + 27.

User Shmnff
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.